IDIOM MUSIK KLASIK DI GEREJA KARISMATIK - Michael Hari Sasongko (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2018)
Church music has long history and experiences in its periods. It began when they, the believers, mentioned themselves as the “Christian”. From the time that phenomenon the christians commenced their act of devotion tradition included their musical tradition of worship. The existence of church music more developed till Middle Age or Dark Age Period. It was dominantly covering to others music genre. At the Renaisance Period, the church reformation movement occured and it was pioneered by Martin Luther. Western music changed at the time. Luther changed of scene; He changed the tradition of Catholic church that used Latin lirics to folk language; He changed the gregorian chant tradition with folksong. The phenomenon was the first time of event of inculturation in world history of music after it undergone stagnancy during the authorization of Roman empire, especially when Pope Gregory created the standarization to all christian music. At the present day we are familiar with charismatic music tradition which is developed from American music tradition. It has a characteristic which is used as the band instrument in praise and worship by christian believers. But sometimes, the believers also use arpeggio or broken-chord as the main charracter on Classical Period in part the way of Western music history. Pass through the reasearch, the reasearcher look into the idioms are used in praise and worship in charismatic church. The reasearcher found that the using of idiom in Classical Period has enriched the nuance of music aesthetic in praise and worship.